2012
DOI: 10.22495/cocv9i2art2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between free cash flow, debt policy and structure of governance: Three stage least square simultaneous model approach: evidence from the Tunisian stock exchange

Abstract: This research tests the efficiency of the ownership structure and the debt policy as mechanism of resolution of agency conflicts between shareholders and managers due to the problem of overinvestment, in the limitation of the problem of the free cash flow, by estimating three stage least square simultaneous model and on the basis of a sample of 35 non-financial Tunisian listed companies selected for the period 1999–2008. Our results are in favour of the theory of free cash flows of Jensen (1986) that stipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The result also shows that ownership (1 if owned by state and 0 otherwise) is significant at explaining ROA and ROE (P value: 0.000 in both cases). This significant negative result is in agreement with the agency theory argument that managers of state owned firms are inefficient due to the lack of market monitoring [37]. It may also be because managers of state owned companies may not face as much pressure from the environment as managers of private companies.…”
Section: Other Variablessupporting
confidence: 83%
See 2 more Smart Citations
“…The result also shows that ownership (1 if owned by state and 0 otherwise) is significant at explaining ROA and ROE (P value: 0.000 in both cases). This significant negative result is in agreement with the agency theory argument that managers of state owned firms are inefficient due to the lack of market monitoring [37]. It may also be because managers of state owned companies may not face as much pressure from the environment as managers of private companies.…”
Section: Other Variablessupporting
confidence: 83%
“…It may also express that highly profitable firms have less need of external funds. This significant negative relationship between debt ratio and firm performance does not support the agency theory and [12]; [36]; [3] and [37] argument that debt disciplines management (by inducing monitoring by lenders) and hence improves performance. But the inverse relationship between debt ratio and firm performance is similar with the finding of [50] conducted on UAE firms using cross-sectional analysis.…”
Section: Debt Policymentioning
confidence: 72%
See 1 more Smart Citation
“…DeAngelo and DeAngelo (2000) and La Porta et al (2000) also reached similar conclusions, which were also confirmed by Aigner et al (1977). The thesis that external financing or dividends reduce free cash flow available to managers has been empirically supported by Lang, Ofek, and Stulz (1996), Li and Cui (2003), Byrd (2010), Khan, Kaleem, and Nazir (2012), Fatma andChichti (2011) andZhang (2009) and by Kadioglu and Yilmaz (2017) in the Turkish context. Titman et al (2003), Fairfield et al (2003) and Dechow et al (2008) put forth that in the case of free cash flow in the control of managers or overinvestment with these funds, company performance is negatively affected.…”
Section: Literature Reviewmentioning
confidence: 55%
“…Debt provides shielding against free cash flow agency costs by reducing free cash flow and hindering management to maximize its interests. The above mentioned by previous research conducted by Afza and Mirza [26], Fatma and Chichti [4], Zhang [28], Utami and Inanga [25]. H2 = There is influence of Free Cash Flow to Leverage…”
Section: B Effect Of Free Cash Flow On Leveragementioning
confidence: 84%